Specific absorption rate in the human head due to metal-frame glasses and ear prosthesis - Mohd Hafizuddin Mat (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2015)
The research in this thesis involves the investigation of the specific absorption rate (SAR) in a human head model exposed to electromagnetic fields. The SARs (1-g and 10-g) were compared inside various models of the human head. Investigation is aimed at the study of the effect of the use of a realistic implant retained prosthetic ear attached to the side of the head and metal-frame glasses. A set of dipole antennas operating at a common frequency of 900, 1800 and 2100 MHz were rotated to investigate the effect of frequency and polarization.